Answer: e = -2 Step-by-step explanation: first, i removed the parentheses. 6 + 0.75e = 2 – 1.25e then, i moved the terms. 0.75 e + 1.25e = 2 – 6 next, i collected the like terms and calculated them. 2e = -4 finally, i divided both sides. e = -2 Log in to Reply

Answer:12 1314

Step-by-step explanation:i guess this should be the abswer

Answer:

e = -2Step-by-step explanation:

first, i removed the parentheses.6 + 0.75e = 2 – 1.25e

then, i moved the terms.0.75 e + 1.25e = 2 – 6

next, i collected the like terms and calculated them.2e = -4

finally, i divided both sides.e = -2